Five new species of Saussurea (Asteraceae, Cardueae) from the Hengduan Mountains region, southwestern China - Chen, You-Sheng (Phytotaxa, 2014)
Based on both herbarium and field observations, five new species of Saussurea (Asteraceae, Cardueae) from the Hengduan Mountains region, southwest China, namely S. fuscipappa, S. liangshanensis, S. pseudorockii, S. qamdoensis, and S. xiaojinensis, are described and illustrated.